Shaking off the ‘Other’: Appropriation of marginalized cultures and the ‘Harlem Shake’ - Steele, Catherine Knight (AoIR Selected Papers of Internet Research, 2013)
The recent Harlem Shake viral meme points to an intersection between the potential participatory promise of memetic content online and hegemonic appropriation of marginalized culture by the dominant group. The meme, while making use of the name ‘Harlem Shake’ does not draw upon the dance which originated in Harlem in the 1980s which was popularized in the 1990s. This paper traces by means of textual analysis the origins of the dance, the release of the 2012 song, the 2013 memes and the reaction video created using interview from actual Harlem residents. Drawing upon the idea of misappropriation and ‘eating the other’, this internet phenomenon allows us to address the ways in which participatory culture can serve to further marginalize rather than liberate. This case follows similar patterns within the historical legacy of commodification of Black culture and causes us to complicate our sometimes overly optimistic notions of participatory culture online.